Peran CSR Awards terhadap Citra Perusahaan dalam Komunikasi Antar Budaya - Susi Andrini (Inter Komunika, 2018)
This study aims to study empirically the influence of Corporate Social Responsibility (CSR) Awards on Corporate Image in intercultural communication, for CSR Indonesia Summit & Awards 2018 case study conducted by MePRindo Communication and Media CSR-Indonesia. The sample used in this study there are 75 respondents taken from participants in the event. The method used in this study is observation (observation) with the type of research and qualitative descriptive qualitative. This study aims to reveal the facts, circumstances, phenomena, variables and circumstances that occur when the study runs. The purpose of this study is to find out how researchers can process the results of research by analyzing the relationship or the relationship between the two, on research CSR Award role against corporate / corporate image in intercultural communication, with quantitative and qualitative descriptive approach. This method is suitable because it only provides an overview of research related to the role of csr awards to corporate image in case study (CSR Indonesia Summit & Awards 2018). Data collection techniques were conducted through the observation stage, questionnaire distribution, interview and documentation study. The analytical technique used in this study, is quantitative and qualitative descriptive. Analytical techniques used in this study, is descriptive quantitative and qualitative. Quantitative research is intended to process data in the field then distribute it into the form of frequency / percentage tabulation, while to deepen the results of quantitative research conducted with qualitative research. The results of the research findings are to obtain in-depth results in analyzing or interpreting the data obtained from the results of the study.